Catalog of the anomuran and brachyuran crabs (Crustacea: Decapoda: Anomura, Brachyura) of the Hawaiian Islands - Castro, Peter (Zootaxa, 2011)
A total of 68 species of anomuran and 284 living species of brachyuran crabs are listed as reliably occurring in the Hawaiian Islands. These figures include 12 species of brachyurans known to have been introduced, but not four species of anomurans and nine brachyurans whose identifications are questionable and two species of anomurans and 14 brachyurans that appear to have been recorded from the islands in error. Five species of anomurans and one brachyuran so far only known from the Midway Islands are included in the total number of Hawaiian species, but not five species of brachyurans only known from Johnston Atoll that are included only for their biogeographical interest. The Hawaiian crab fauna shows a predominance of wide ranging Indo-West Pacific species (41% of Anomura, 58% of Brachyura), some degree of endemicity (37% of Anomura, 14% of Brachyura), but it is much impoverished in terms of total number of species when compared with the crab fauna of the Indo-Malayan Archipelago, regarded as a center of diversification for many marine taxa. Several taxonomic changes are also made: Trapezia neglecta Castro, 2003, is ascertained to be a junior synonym of T. intermedia Miers, 1886, and a lectotype and a paralectotype are selected for Grapsus oceanicus Hombron & Jacquinot, 1846 (Grapsidae).